2009
DOI: 10.1053/j.gastro.2008.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Types and Sociodemographic Characteristics as Risk Factors for Barrett's Esophagus

Abstract: Background & Aims-Little is known about the effects of alcohol use and sociodemographics on the risk of Barrett's esophagus, a precursor to esophageal adenocarcinoma. We evaluated the association between alcohol use, alcohol type, sociodemographic profiles, other lifestyle factors and the risk of Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 37 publications
8
68
0
1
Order By: Relevance
“…Any smoking during a patient's lifetime was associated with a greater risk for BE compared with non-GERD controls (OR 1.4, 95% CI 1.2-1.7), but not when compared with patients with chronic GERD (OR 1.2, 95% CI 0.8-1.9), suggesting that the increased risk of BE associated with tobacco usage may be mediated via increasing GERD ( 35 ). In contrast to tobacco usage, alcohol consumption has not been demonstrated to be signifi cantly associated with the risk for development of BE ( 36,37 ). In fact, there are data suggesting a possible protective eff ect of wine consumption, with ORs ranging from 0.44 (95% CI 0.2-0.99) to 0.71 (95% CI 0.52-0.98) ( 37,38 ).…”
Section: Summary Of Evidencementioning
confidence: 94%
See 1 more Smart Citation
“…Any smoking during a patient's lifetime was associated with a greater risk for BE compared with non-GERD controls (OR 1.4, 95% CI 1.2-1.7), but not when compared with patients with chronic GERD (OR 1.2, 95% CI 0.8-1.9), suggesting that the increased risk of BE associated with tobacco usage may be mediated via increasing GERD ( 35 ). In contrast to tobacco usage, alcohol consumption has not been demonstrated to be signifi cantly associated with the risk for development of BE ( 36,37 ). In fact, there are data suggesting a possible protective eff ect of wine consumption, with ORs ranging from 0.44 (95% CI 0.2-0.99) to 0.71 (95% CI 0.52-0.98) ( 37,38 ).…”
Section: Summary Of Evidencementioning
confidence: 94%
“…In contrast to tobacco usage, alcohol consumption has not been demonstrated to be signifi cantly associated with the risk for development of BE ( 36,37 ). In fact, there are data suggesting a possible protective eff ect of wine consumption, with ORs ranging from 0.44 (95% CI 0.2-0.99) to 0.71 (95% CI 0.52-0.98) ( 37,38 ).…”
Section: Summary Of Evidencementioning
confidence: 96%
“…Alcohol consumption, and its possible relationship with BE, has been studied in a few case-control studies. Null associations with alcohol have been observed (15,17), and one study (18) found alcohol to be a risk factor. Inverse associations have been reported for wine consumption (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Although some previous studies have shown inverse correlation with wine use 32,33 but positive correlation with liquor use 34 and BE development, some authors have argued that alcohol itself, not the type of the different drinks, was directly related to GERD. 35 Our study found a significant relationship between BE and alcohol abuse and tobacco use, and demonstrates that BE development increases with alcohol abuse and smoking.…”
Section: Discussionmentioning
confidence: 96%